PLANEACIÓN FINANCIERA A AUTOLATERÍA Y ACCESORIOS ELECTRICAR DE LA CIUDAD DE LOJA DURANTE EL PERIODO COMPRENDIDO 2016-2018 - Ayala Jaramillo, Karen Betzabeth (2016)
The present work of thesis consists in carrying out a financial planning for Autolatería and Accessories ELECTRICAR of the City of Loja during the period between 2016-2018, with the purpose of anticipating the financial position for an adequate decision making, for which it was necessary the objectives. It began with the compilation of financial information of the company through the financial statements of the year 2015, followed by a vertical analysis to know the financial and economic structure and analyzed each of the accounts against the group they belong to; Also through the application of financial indicators of liquidity, activity, indebtedness and profitability was verified the compliance of the policies and presented the deficiencies found in the Financial-Economic Diagnosis. The previous financial analysis allowed the development of forecasts of sales and purchases to know the needs of the company, with that was formulated a cash planning considering administrative, financial and selling expenses. Based on the results obtained, pro-forma financial statements were prepared, in which the financial resources requirements were established in advance; The procedures were carried out through the percentage sales and percentage increase methods that are adjusted to the 5 needs of the company, based on the historical values presented in the financial statements for the year 2015. In order to complement the financial planning work carried out, the Balance Point was applied, which shows a downward trend towards the last year of projection in the level of expenses and an increase in sales revenue of the company, which allows to develop a Investment proposal to acquire a building with better installed capacity, which is valued through evaluation criteria obtaining a positive NPV and a high IRR that reflect the viability of the project and its opportunity to strengthen the economic benefits, the profitability of the Financial structure and operational activity. Finally, the thesis work is concluded with the presentation of Conclusions and Recommendations resulting from the work done, which will be a great help for decision making.